2011
DOI: 10.1371/journal.pone.0028406
|View full text |Cite
|
Sign up to set email alerts
|

Balance between MKK6 and MKK3 Mediates p38 MAPK Associated Resistance to Cisplatin in NSCLC

Abstract: The p38 MAPK signaling pathway has been proposed as a critical mediator of the therapeutic effect of several antitumor agents, including cisplatin. Here, we found that sensitivity to cisplatin, in a system of 7 non-small cell lung carcinoma derived cell lines, correlated with high levels of MKK6 and marked activation of p38 MAPK. However, knockdown of MKK6 modified neither the response to cisplatin nor the activation of p38 MAPK. Deeper studies showed that resistant cell lines also displayed higher basal level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 53 publications
2
36
1
Order By: Relevance
“…Similar to cyclophilin overexpression in cancer, an increase in p38MAPK phosphorylation has also been found in different tumours, which in turn correlates with poor prognosis and resistance to cisplatin treatment. 9,10,25,27 Considering the strong correlation among p38MAPK, cyclophilins and sensitivity to cisplatin, we next speculated that p38-dependent sensitivity of tumour cells to cisplatin could be, at least in part, mediated through CypAdependent isomerisation of Pro224.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to cyclophilin overexpression in cancer, an increase in p38MAPK phosphorylation has also been found in different tumours, which in turn correlates with poor prognosis and resistance to cisplatin treatment. 9,10,25,27 Considering the strong correlation among p38MAPK, cyclophilins and sensitivity to cisplatin, we next speculated that p38-dependent sensitivity of tumour cells to cisplatin could be, at least in part, mediated through CypAdependent isomerisation of Pro224.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that ROS leads to increases in the phosphorylation of ERK and p38 MAPK [26][27][28]. Cisplatin generates hydrogen peroxide (H 2 O 2 ), a relatively long-lived species of ROS, in a variety of cells including macrophages [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…For the NSCLC, in which EGFR exhibits overexpression or aberrant activation in 50-90% of cancer cells (Larsen and Minna, 2011), Eva M. Galan-Moya et al demonstrated by innovatively using transformed cell lines that the interplay between MAPKKs was crucial for p38 MAPK activation in response to cDDP (Cisplatin) and proposed that the imbalance between MKK6 and MKK3 could be a potential biomarker for NSCLL, while MKK3, but not MKK6, was the critical player, although MKK3 controls MKK6 levels in NSCLC derived cell lines through activation of p38 MAPK (Galan-Moya et al, 2011).…”
Section: Mapk and Lung Cancermentioning
confidence: 99%